Single-Axis solar tracking system - Salhab, Mahmoud (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2017)
Energy crisis is the most important issue in todays world . converntional energy resources are not only limited but also the prime culprit for environmental pollution.
no of pages 65, 30300, 27/2017ميكانيك, in the store
Keywords: Solar, single